1963
DOI: 10.1192/bjp.109.462.680
|View full text |Cite
|
Sign up to set email alerts
|

The Genesis of Schizophrenic Thought Disorder: A Serial Invalidation Hypothesis

Abstract: The study to be reported was carried out within the framework of Personal Construct Theory as put forward by Kelly (1955). This theoretical background is summarized and discussed in Bruner (1956) and Bannister (1962).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
56
1

Year Published

1966
1966
2009
2009

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 115 publications
(58 citation statements)
references
References 4 publications
1
56
1
Order By: Relevance
“…This is not entirely surprising since there is experimental evidence that the process which tends to lead to loose construing (lower Intensity) also tends to lead to repeated radical changes in the pattern of construing (cf. the discussion on the effect of serial invalidation in Bannister, 1963 and1965). However, as will be seen later from the graph plot of results (Fig.…”
Section: Relationship Between Consistency and Intensitymentioning
confidence: 87%
See 3 more Smart Citations
“…This is not entirely surprising since there is experimental evidence that the process which tends to lead to loose construing (lower Intensity) also tends to lead to repeated radical changes in the pattern of construing (cf. the discussion on the effect of serial invalidation in Bannister, 1963 and1965). However, as will be seen later from the graph plot of results (Fig.…”
Section: Relationship Between Consistency and Intensitymentioning
confidence: 87%
“…Stemming as they do from an elaborate theoretical framework, they can be used in building up explanations of the psychological processes involved in becoming thought disordered (Bannister, 1963 and1965).…”
Section: A Grid Test Of Schizophrenic Thought Disoraje~mentioning
confidence: 99%
See 2 more Smart Citations
“…Bannister (1960) In a retest of the hypothesis (Bannister, 1965), he found that validation led to increased relationships between constructs, but invalidation produced no change, as if subjects were resisting a change that would leave them with no alternative system. However, if, of two constellations of constructs, one was validated and the other constellation repeatedly invalidated, then the appropriate increase or de crease in the relationships of constructs within the constellation occurred.…”
Section: Schiz2ehrenia_an^personal_çoeistruçtsmentioning
confidence: 99%